THE INTRINSIC ELEMENTS OF REMBULAN TENGGELAM di WAJAHMU - Mahuda Safitri; SIlvi Nuril Maulidia; Rama Garetha Evansam; Aisyah Brilliant; Ahmad Siswanto; Rahmania Firdaus (Universitas Islam Balitar, 2017)
This analysis aims to describe the social values ​​contained in the novel